Making Sense of Race, Class, and Gender : Commonsense, Power, and Privilege in the United States - Pascale, Celine-Marie, 1956- (Taylor and Francis, 2013)
Using arresting case studies of how ordinary people understand the concepts of race, class, and gender, Celine-Marie Pascale shows that the peculiarity of commonsense is that it imposes obviousness-that which we cannot fail to recognize. As a result, how we negotiate the challenges of inequality in the twenty-first century may depend less on what people consciously think about ""difference"" and more on what we inadvertently assume. Through an analysis of commonsense knowledge, Pascale expertly provides new insights into familiar topics. In addition, by analyzing local practices in the cont.